HUBUNGAN ANTARA KECERDASAN EMOSIONAL DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR BIOLOGI SISWA - NURLIA NURLIA (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2018)
The students’ learning results are influenced by two factors, namely internal and external factors. The internal factors that can influence learning results are emotional intelligence and learning motivation. The research aims to discover the relation of emotional intelligence and learning motivation with Biology learning results of the students at SMAN 3 Luwuk in Banggai District.The research is ex post facto. The population of the research were the students of class IPA at SMAN 3 Luwuk in Banggai District of academic year 2017/2018. The samples were 264 students taken by using stratified random sampling technique. Data were collected by employing questionnaire and documentation. The data of the research were analyzed by using descriptive and inferential statistics techniques. The results of the research reveal that (i) the students’ emotional intelligence is in high category, (ii) the students’ learning motivation is in high category, (iii) the students’ Biology learning results is in high category, (v) there is fairly strong relation between emotional intelligence and the students’ Biology learning results, (vi) there is fairly strong relation between learning motivation and the students’ Biology learning results, and (viii) there is strong relation between emotional intelligence and learning motivation toword Biology learning results of the students at SMAN 3 Luwuk in Banggai District.